Inflammasome activation by Pseudomonas aeruginosa's ExlA pore‐forming toxin is detrimental for the host. (6th September 2020) - Bouillot, Stéphanie; Pont, Stéphane; Gallet, Benoit; Moriscot, Christine; Deruelle, Vincent; Attrée, Ina; Huber, Philippe
Abstract: During acute Pseudomonas aeruginosa infection, the inflammatory response is essential for bacterial clearance. Neutrophil recruitment can be initiated following the assembly of an inflammasome within sentinel macrophages, leading to activation of caspase‐1, which in turn triggers macrophage pyroptosis and IL‐1β/IL‐18 maturation. Inflammasome formation can be induced by a number of bacterial determinants, including Type III secretion systems (T3SSs) or pore‐forming toxins, or, alternatively, by lipopolysaccharide (LPS) via caspase‐11 activation. Surprisingly, previous studies indicated that a T3SS‐induced inflammasome increased pathogenicity in mouse models of P. aeruginosa infection. Here, we investigated the immune reaction of mice infected with a T3SS‐negative P. aeruginosa strain (IHMA879472). Virulence of this strain relies on ExlA, a secreted pore‐forming toxin. IHMA879472 promoted massive neutrophil infiltration in infected lungs, owing to efficient priming of toll‐like receptors, and thus enhanced the expression of inflammatory proteins including pro‐IL‐1β and TNF‐α. However, mature‐IL‐1β and IL‐18 were undetectable in wild‐type mice, suggesting that ExlA failed to effectively activate caspase‐1. Nevertheless, caspase‐1/11 deficiency improved survival following infection with IHMA879472, as previously described for T3SS+ bacteria. We conclude that the detrimental effect associated with the ExlA‐induced inflammasome is probably not due to hyperinflammation, rather it stems from another inflammasome‐dependent process.